New archaeometrical results related to Neolithic blueschist stone tools from Borsod-Abaúj-Zemplén County, Hungary. (February 2018) - Kereskényi, Erika; Szakmány, György; Fehér, Béla; Kasztovszky, Zsolt; Kristály, Ferenc; Rózsa, Péter
Abstract: 26 blueschist Neolithic polished stone tools coming from archaeological sites in Borsod-Abaúj-Zemplén County (NE Hungary) were archaeometrically analysed. All items were described and documented macroscopically and magnetic susceptibility was measured on each tool. Non-destructive XRD analyses were made on all implements to separate blueschists from other metamorphic rocks, because this technique can make a difference between the diagnostic sodic amphiboles and other amphiboles, which was confirmed by EDS/SEM in each case. Electron microprobe analyses were carried out on polished sections and selected intact axes by using "original-surface" method. Non-destructive Prompt Gamma Activation Analysis (PGAA) was performed on selected pieces. Blueschist polished stone tools were classified into five groups based on their mineral components and metamorphic evolution. Mineral chemistry analyses suggest that blueschists suffered a polyphase metamorphism. Our data were compared to the nearest blueschist outcrop in the Meliata Unit (Slovakia); it is supposed that the source area of the blueschist implements is the Meliata Unit and/or the blueschist pebbles from Cretaceous conglomerate in the Pieniny Klippen Belt. Highlights: Blueschist implements are restricted to the northern region in Hungary. Five groups of blueschist polished stone tools were distinguished. The source area of the implements is the Meliata Unit and the Pieniny Klippen Belt.